Disentangling the effects of depression and perceived stress on cortisol levels in individuals with obesity. (September 2021) - Mariani, N.; McLaughlin, Anna; Lambert, Ellen; Kose, Melisa; Patsalos, Olivia; Bogdanova, Anna; Ferraro, Luca; Chamseddine, Ghassan; Panagiotopoulos, Spyros; Chang, Avril; Ramar, Sasindran; Patel, Ameet; et al.
Abstract : Background: Hypothalamic-pituitary-adrenal (HPA) axis dysregulation is suggested to play a role in the association between depression and obesity. We investigated differences in cortisol levels in individuals with obesity with and without depression, and the effects of perceived stress and binge eating on cortisol levels. Methods: Saliva samples were collected at awakening, 15, 30 and 60 minutes post-awakening from 84 individuals with obesity (44 controls and 41 with major depressive disorder). Salivary cortisol was analysed using ELISA technique. Linear Mixed Model was used for group differences in cortisol awakening response (CAR) with adjustment for confounders and binge eating. Results: Individuals with obesity and depression had lower CAR compared with controls with obesity (B=-0.44;p=0.04). However, after controlling for perceived stress, depression no longer influenced CAR (B=-0.09;p=0.75), but individuals with moderate/high stress had lower CAR compared with those with low stress (B=-0.63;p=0.03). Binge eating did not affect CAR (B=-0.08;p=0.46). Conclusions: Our results suggest that, in our sample, differences in CAR between depressed and controls appear to be due to higher levels of perceived stress in depressed patients.